2008
DOI: 10.1186/1476-9255-5-2
|View full text |Cite
|
Sign up to set email alerts
|

Does CD4+CD25+foxp3+ cell (Treg) and IL-10 profile determine susceptibility to immune reconstitution inflammatory syndrome (IRIS) in HIV disease?

Abstract: HIV-specific T-lymphocyte responses that underlie IRIS are incomplete and largely remain hypothetical. Of the several mechanisms presented by the host to control host immunological damage, Treg cells are believed to play a critical role. Using the available experimental evidence, it is proposed that enormous synthesis of conventional FoxP3 -Th cells (responsive) often renders subjects inherently vulnerable to IRIS, whereas that of natural FoxP3 + Treg cell synthesis predominate among subjects that may not prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 48 publications
1
21
0
1
Order By: Relevance
“…Although IRIS is associated with certain infectious and non‐infectious conditions (Shankar et al ., ), the morbidity associated with HIV/TB co‐infection is significantly higher than for the other conditions. HIV‐infected patients with low CD4+ T‐cell counts ‘immunologically’ tolerate the presence of the tubercle bacilli as the host is unable to mount an inflammatory response (Shankar et al ., , b). Tuberculosis‐associated IRIS is considered critical in developing countries, where the proportion of HIV/TB IRIS is reportedly high, ranging from 10% to 43% (Breton et al ., ; Shelburne et al ., ; Murdoch et al ., ; Haddow et al ., ).…”
Section: Tuberculosis and Immune Restitution Inflammatory Syndromementioning
confidence: 99%
“…Although IRIS is associated with certain infectious and non‐infectious conditions (Shankar et al ., ), the morbidity associated with HIV/TB co‐infection is significantly higher than for the other conditions. HIV‐infected patients with low CD4+ T‐cell counts ‘immunologically’ tolerate the presence of the tubercle bacilli as the host is unable to mount an inflammatory response (Shankar et al ., , b). Tuberculosis‐associated IRIS is considered critical in developing countries, where the proportion of HIV/TB IRIS is reportedly high, ranging from 10% to 43% (Breton et al ., ; Shelburne et al ., ; Murdoch et al ., ; Haddow et al ., ).…”
Section: Tuberculosis and Immune Restitution Inflammatory Syndromementioning
confidence: 99%
“…Chronic CNS-IRIS in HIV infected individuals may contribute to the development of HAND due to CNS damage caused by prolonged immune activation (reviewed in (Johnson and Nath 2011)). HIV infected individuals who do not mount an effective T reg response after cART initiation may be more prone to develop IRIS due to ineffectual suppression of hyperimmune responses after reconstitution of the immune system (Shankar et al 2008; Martin-Blondel et al 2012). During the chronic form of CNS-IRIS, elevated extracellular dopamine as a result of drug abuse may inhibit T reg function within the CNS, exacerbating this chronic immune activation and the development of HAND.…”
Section: Dopamine and Hiv In T Cellsmentioning
confidence: 99%
“…14 Additionally, it has been shown that numbers of naturally occurring Foxp3+ T regulatory cells are increased in patients in which IRIS does not develop, whereas patients in which IRIS develops normally elicit Th-0 cell and effector T cells responses, which produce pro-inflammatory cytokines in response to cellsignaling factors. 15 Our data show that the frequency of CD4 + CD25 + FOXP-3 + T cells in peripheral blood was low (1.82%) when compared with levels in healthy persons (5-10%). Therefore, although T regulatory cells were present, they were not sufficient to control establishment of ulcerated lesions or onset of systemic manifestations, which culminated in a comatose state.…”
Section: Discussionmentioning
confidence: 94%